The Georgian Hyperinflation and Stabilization - Wang, Jian-Ye (IMF Working Papers; Working Paper ;, 1999)
This paper anlayzes the Georgian hyperinflation of 1993-94, which featured endogenous fiscal expenditures and the money supply, depreciation, and currency substitution. Hyperinflation was stopped by removing generalized consumer subsidies and tightening of monetary policy, and not by a sudden rush of credibility or imposition of an exchange rate anchor. A de facto exchange rate anchor served ex post as a vehicle for building credibility, which ensured a dramatic reversal of currency substitution when the currency reform was implemented. The paper also discusses the relatively rapid output recovery in Georgia.